A critical cognitive analysis of Japan’s nuclear contaminated water discharge discourse - Sun, Chengzhi; Wang, Chengyi; Liu, Wenyu (Frontiers in Communication, 2024)
This study, grounded in Critical Cognitive Linguistics (CCL), critically examines the discourse surrounding the Fukushima nuclear-contaminated water discharge, focusing on the use of compound image schemas in environmental risk communication. By analyzing editorials from Asahi Shimbun, this research reveals how discourse producers, from government bodies to media outlets, employ image schemas to navigate, shape, and legitimize their stances on this contentious issue. The investigation identifies the prevalent use of PATH and CONTAINER schemas, which facilitate the construction of complex narrative spaces that define "in-group" and "out-group" dynamics, thereby guiding public perception and discourse participation towards an implicit endorsement of specific policy directions. The findings highlight the dynamic interplay between micro-level discourse strategies and macro-level cognitive frameworks, projecting tailored narratives into the public sphere. This projection, rooted in sophisticated cognitive mechanisms, illustrates the strategic use of discourse to influence public opinion and legitimize environmental policy decisions, reflecting broader social implications and the power of discourse in shaping environmental risk perceptions.